RESEARCH OF ASH-SLAG MIXTURES FOR PRODUCTION OF CONSTRUCTION MATERIALS - Islombek Akhmedov,Adxamjon Khamidov,Yusupov Shavkat,Zayniddin Jalalov,Isroiljon Umarov,Aleksandr Kazadayev (Journals Park Publishing, 2022)
The article deals with the use of ash-slag mixtures in the production of building materials, presents the results of studies to determine the physical and mechanical characteristics of solutions prepared from various compositions.
Keywords: Concrete, binder, cement, ash-slag mixtures, plasticizing additives, sulfite-yeast stillage, super-plasticizers.